2005
DOI: 10.2105/ajph.2004.051318
|View full text |Cite
|
Sign up to set email alerts
|

A Model for a Regional System of Care to Promote the Health and Well-Being of People with Rare Chronic Genetic Disorders.

Abstract: People with rare, inherited chronic health conditions, such as hemophilia, face added physical, social, emotional, and fiscal challenges beyond those that are common to more prevalent chronic conditions. In 1975, a partnership among clinicians, consumers, and government agencies created a nationwide regional health delivery system that increased access to clinical care, prevention, and research, thereby improving health outcomes for people with hemophilia in the United States. Today, more than 130 Comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 26 publications
(12 reference statements)
1
64
0
1
Order By: Relevance
“…The regionalized HTCs, a multi-disciplinary, team-based care delivery model, have been implemented in the US for several decades with goals to prevent orthopedic complications and to maximize the physical and psychological functioning and socioeconomic benefits for this rare disease population 18 . HTC care has been shown to be associated with lower mortality 19 and fewer bleed-related hospitalizations 20 compared with care obtained elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The regionalized HTCs, a multi-disciplinary, team-based care delivery model, have been implemented in the US for several decades with goals to prevent orthopedic complications and to maximize the physical and psychological functioning and socioeconomic benefits for this rare disease population 18 . HTC care has been shown to be associated with lower mortality 19 and fewer bleed-related hospitalizations 20 compared with care obtained elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…2 Care for individuals with hemophilia in the U.S. is delivered principally via a network of comprehensive hemophilia treatment centers (HTCs). More than 130 HTCs receive federal support to establish and maintain multidisciplinary teams to provide prospective, preventive, and family-centered surveillance and management of this rare chronic genetic blood coagulation disorder, 3 including data collection on outcomes related to hemophilia.…”
Section: Introductionmentioning
confidence: 99%
“…A network of hemophilia treatment centers (HTCs) was developed in 1975 with federal funding to provide comprehensive multidisciplinary care to people with hemophilia in the U.S. [3]. Data from the HSS showed that about 70% of all people with hemophilia were receiving some care from these centers in the early 1990s.…”
Section: Surveillance and Hemophiliamentioning
confidence: 99%